Removal of cadmium from waters by adsorption using nanochitosan. Issue 3 (May 2020) - Alyasi, Haya; Mackey, Hamish R; McKay, Gordon
This study is based on the removal of cadmium from water by adsorption onto nanochitosan in order to reduce the impact of cadmium toxicity to humans and animals. The adsorption of cadmium onto this particular nanochitosan is a novel study assessed through equilibrium and kinetic experiments. It provides an effective method of cadmium removal to avoid cadmium health impacts described herein. The influence of different parameters on the effectiveness and efficiency of cadmium adsorption onto nanochitosan are presented by studying the effects of pH, initial cadmium concentration and the dosage of nanochitosan. Commonly used equilibrium models are described, and the discussion focuses on an analysis of different isotherm and kinetic models to determine the best fit model for predicting the cadmium–nanochitosan adsorption capacity. All models were studied for their statistical significance using two error methods; the Sum of Squared Error to the natural experimental data and the R 2 method to the linearised experimental data. Since the R 2 values were very close, the best fit is described according to the findings of the minimum Sum of Squared Error values. The capacity of nanochitosan was found to be 1.96 mmol Cd/g adsorbent. Most previous research studies propose a Langmuir equilibrium model for the adsorption of cadmium on chitosan and nanochitosan; however in the present study, three isotherms were tested; the best fit isotherm was the SIPS followed by the Langmuir, and the best fit kinetic model was the pseudo-second order followed by the Elovich model. The SIPS model indicates a multiple adsorption mechanism, a second-order chemisorption mechanism with two main complexation bonding methods, namely, a complex with one amine functional group and a second complexing type with two amine groups and two hydroxyl groups.